Scientific response to a cluster of shark bites. Issue 4 (13th May 2022) - Barnett, Adam; Fitzpatrick, Richard; Bradley, Michael; Miller, Ingo; Sheaves, Marcus; Chin, Andrew; Smith, Bethany; Diedrich, Amy; Yick, Jonah Lee; Lubitz, Nicolas; Crook, Kevin; Mattone, Carlo; et al.
Abstract: Shark bites are of high public concern globally. Information on shark occurrence and behaviour, and of the effects of human behaviours, can help understand the drivers of shark‐human interactions. In Australia, a number of shark bite clusters occurred over the last decade. One of these took place in Cid Harbour the Whitsundays, Queensland, a region for which little was known about the shark community. Here, we describe and evaluate the research in response to that shark bite cluster. Fishing methods, acoustic and satellite tracking, and baited remote underwater video cameras (BRUVs) were used to identify the shark species using Cid Harbour, estimate relative abundance, and describe habitat use and residency. Side‐scan sonar and BRUVs were also used to assess prey availability. Recreational users were surveyed to understand human behaviour and their awareness and perceptions of 'Shark Smart' behaviours. This allowed shark occurrence and behaviour to be interpreted in the context of human behaviours in the Harbour. Eleven shark species were identified. Relative abundance was not unusually high, and residency in Cid Harbour was typically low. For example, 79% of acoustically tagged sharks visited the harbour on <10% days at liberty. Shark prey was available year‐round. Notably, anchored boats regularly conduct activities that can attract sharks (dumping food scraps, provisioning and cleaning fish). Alone, the methods used in this study had variable success, but combined they provided a large amount of complementary information. Including a social science component in the research response to the shark bite incidents allowed for a more holistic understanding of the Cid Harbour bite incidents. This study did not identify anything unusual about the shark community that could have contributed to the Cid Harbour shark bite cluster. However, the three incidents involved people bitten almost instantly after entering the water, which is unusual and suggests that feeding/attracting sharks to boats could have been a contributor and also that any species capable of biting humans could have been responsible. The eradication of activities that attract sharks to areas where people enter the water may reduce shark bite risk. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.